Cardiopulmonary Resuscitation Guideline Update: A Systematic Review - Atmojo, Joko Tri; Widiyanto, Aris; Handayani, Rina Tri (Indonesian Journal of Medicine, 2019)
Background: Every five years, the American Heart Association (AHA) releases new guidelines on CPR. Previous guidelines have focused on Airway-Breathing-Circulation (ABC) advocacy. However, in 2010 guidelines for CPR recommended changes in the sequence of BLS steps to CAB (chest compression, airway, and breathing) for adults, children and infants (excluding newborns). The purpose of this review is to explain the reasons and provide scientific evidence about the results of CAB actions compared to ABC.Subjects and Method: Systematic reviews were done by searching the database through PubMed, Google Scholar, and Science Direct. Key words for this review include: AHA Guideline AND CPR 2010, CAB in CPR, CAB, and RCT (Randomized Controlled Trial) guidelines and why does ABC turn into CAB? The inclusion criteria are systematic reviews, clinical reviews and guidelines.Results: The results are in the form of 3 review articles and 1 RCT study. The basic reasons for changing ABC to CAB are (1) The most common case of cardiac arrest in adults, and the initial element of critical BLS (basic life support) is chest compression and early defibrillation by changing sequentially to CAB, chest compression will start faster; (2) Most victims of cardiac arrest outside the hospital do not get CPR observers, this is an obstacle to opening the airway and exhaling; and (3) Chest compression provides vital blood flow to the heart and brain. One RCT study showed that the time to do the first resuscitation with the CAB technique (mean = 25; SD = 10) was faster than the ABC technique (mean = 32; SD = 12) and statistically significant (p = 0.002).Conclusion: Chest compression is the most important aspect of heart attack management because airway maneuver takes a long time. The time to complete the first resuscitation cycle on CAB action is shorter than using ABC actions.Keywords: ABC, CAB, CPR guidelines, systematic reviewCorrespondence: Joko Tri Atmojo. School of Health Sciences Mamba'ul 'Ulum, Surakarta, Jl. Ring Road Utara, Tawangsari, Mojosongo, Jebres, Surakarta, Central Java. Email: jokotriatmojo1@gmail.com. Mobile: +6281393319000Indonesian Journal of Medicine (2019), 4(2): 82-87https://doi.org/10.26911/theijmed.2019.04.02.01